Understanding the Workforce for Diabetes Management with Māori and Pacific Peoples: Using Tangata Hourua as the Framework Method for Analysis of Qualitative Research - Mullane, T; Warbrick, I; Tane, T; Anderson, A; Selak, V; Harwood, M (Nga Pae o te Maramatanga, 2024)
The aim of the study reported in this article was to explore the experiences of (1) people living with type 2 diabetes (T2D) and their whānau, and (2) kai manaaki, community health workers and dieticians who provide care to Māori and Pacific peoples living with T2D in the community. A key objective for this research was for its findings to inform workforce development strategies that will achieve equity for Māori and Pacific peoples with T2D and other long-term conditions. Using the Tangata Hourua framework, a Kaupapa Māori and Pacific research model, the experiences of people enrolled in Mana Tū—a mana-enhancing programme that supports people with poorly controlled T2D to “take charge” of their condition—and their whānau were gathered, analysed and then compared with the experiences of health workers. This approach has yielded new and rich knowledge strongly supporting the view that Māori and Pacific health workers who are based in the community are best positioned to make genuine relationships with Māori and Pacific clients and their whānau.
Keywords: 4203 Health Services and Systems; 42 Health Sciences; Health Services; Clinical Research; Diabetes; 7.1 Individual care needs; 8.1 Organisation and delivery of services; Metabolic and endocrine; 1608 Sociology; 1699 Other Studies in Human Society; 45 Indigenous studies